Anion capture and exchange by functional coatings: New routes to mitigate steel corrosion in concrete infrastructure. (November 2017) - Falzone, Gabriel; Balonis, Magdalena; Bentz, Dale; Jones, Scott; Sant, Gaurav
Abstract: Chloride-induced corrosion is a major cause of degradation of reinforced concrete infrastructure. While the binding of chloride ions (Cl − ) by cementitious phases is known to delay corrosion, this mechanism has not been systematically exploited as an approach to increase structural service life. Recently, Falzone et al. [ Cement and Concrete Research 72, 54–68-(2015)] proposed calcium aluminate cement (CAC) formulations containing NO3 -AFm to serve as anion exchange coating s that are capable of binding large quantities of Cl − ions, while simultaneously releasing corrosion-inhibiting NO3 − species. To examine the viability of this concept, Cl − binding isotherms and ion-diffusion coefficients of a series of hydrated CAC formulations containing admixed Ca(NO3 )2 (CN) are quantified. This data is then input into a multi-species Nernst-Planck (NP) formulation, which is solved for a typical bridge-deck geometry using the finite element method (FEM). For exposure conditions corresponding to seawater, the results indicate that Cl − scavenging CAC coatings (i.e., top-layers) can significantly delay the time to corrosion (e.g., 5 ≤ d f ≤ 10, where d f is the steel corrosion initiation delay factor [unitless]) as compared to traditional OPC-based systems for the same cover thickness; as identified by thresholds of Cl − /OH − or Cl − /NO3 − (molar) ratios in solution. The roles of hindered ionic diffusion, and the (re)passivation of the reinforcing steel rendered by NO3 − are also discussed.